Documentary storytelling making stronger and more dramatic nonfiction films - Bernard, Sheila Curran (Focal Press, 2007)
"Documentary Storytelling is unique in offering an in-depth look at story and structure as applied not to Hollywood fiction, but to films and videos based on factual material and the drama of real life. With the growing popularity of documentaries in today's global media marketplace, demand for powerful and memorable storytelling has never been greater. This practical guide offers advice for every stage of production, from research and proposal writing to shooting and editing, and applies it to diverse subjects and film styles, from verite and personal narrative to archival histories and more." "Filled with real-world examples drawn from the author's career and the experiences of some of today's top documentarians, Documentary Storytelling includes special interview chapters with Ric Burns, Jon Else, Nick Fraser, Susan Froemke, Sam Pollard, Onyekachi Wambu and other film professionals. This second edition has been brought up to date with a more international focus, a look at lower-budget independent filmmaking, and consideration of newer films including Super Size Me, Murderball, So Much So Fast, and When the Levees Broke."--Jacket.
Includes bibliographical references and index. - Print version record
Keywords: Documentary films -- Production and direction; Documentary films -- Authorship; Documentaires; Production et réalisation; Documentary films; Authorship; Documentary films; Production and direction